An Error Analysis Made by the Second Year English Department Students in Translating Advertisement Text - Simalango, Enjelina; Oktavia, Witri (Journal of English Language Teaching, 2025)
This study investigates the types and causes of errors in translating advertisement texts made by second-year English Department students at Universitas Negeri Padang. Use a qualitative descriptive method, the research involved a population of 219 students across 10 classes (K1–K10). A sample of 22 students was selected using cluster random sampling. The instruments used in data collection were a translation test. The findings indicate that the most frequent type of error found in students’ translations from Indonesian to English was deviation of meaning, accounting for 60% of the 35 identified error cases. These results highlight the need for greater emphasis on meaning accuracy in translation teaching and learning processes.